Dehydration and rehydration affect brain regional density and homogeneity among young male adults, determined via magnetic resonance imaging: A pilot self-control trial - Zhang, Na; Zhang, Jianfen; Du, Songming; Ma, Guansheng (Frontiers in Nutrition, 2022)
The effects of dehydration and rehydration on brain regional density and homogeneity are unknown and have been infrequently studied. In this pilot self-control study, twelve participants aged 18-25 years were recruited and the brain was scanned using magnetic resonance imaging for three tests under different hydration statuses. In three tests, urine osmolality was determined to assess hydration status. Test 1 was conducted after 12 h of overnight fasting. Test 2 was conducted in a dehydration state induced by 36 hours of water deprivation. Test 3 was conducted in a rehydration state, which was induced by 1.5 L of purified water supplementation. Compared with test 1, participants under the dehydration state in test 2 had higher cerebrospinal fluid density (p<0.001). Compared with test 2, participants under the rehydration state in test 3 showed an extensive increase in gray matter density in widespread brain regions, mainly involving the left middle temporal gyrus, cuneus, right thalamus, left rolandic opercula, Brodmann area 39, right precentral, left postcentral gyrus, and cingulate gyrus (p<0.001); a higher white matter density in the temporal lobe, sub-lobar, and sub-gyral areas; and a lower cerebrospinal fluid density (p<0.001). The multimodal, multiscale neuroimaging marker of the human brain connection—the regional homogeneity (ReHo) index—was used for evaluating the connectivity of nodes in the brain. Compared with test 1, participants in test 2 had a lower ReHo value in the right amygdala, left occiput median, right lingual, opercula part of right inferior frontal gyrus, and right precuneus (p<0.01). Compared with test 2, participants in test 3 had a higher ReHo value in the right amygdala, right lingual, opercula part of the right inferior frontal gyrus, and right precuneus (p<0.01). Dehydration state increased cere-brospinal fluid density, decreased brain regional homogeneity. Rehydration state increased brain gray matter and white matter density widespreadly, and increased brain regional homogeneity.